2019
DOI: 10.1093/brain/awz257
|View full text |Cite
|
Sign up to set email alerts
|

Handedness, language areas and neuropsychiatric diseases: insights from brain imaging and genetics

Abstract: The brain signature and genetic basis of handedness are unclear. Wiberg et al. show that left-handers have higher functional connectivity between language networks, and identify four genomic regions associated with handedness. Variants within these regions appear, by influencing brain architecture, to predispose both to left-handedness and to certain neuropsychiatric diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 49 publications
10
131
1
3
Order By: Relevance
“…5c ). There are several resting-state connectivity-related IDPs correlated with handedness ( Tables S3 ), consistent with a recent study 30 that also used UKB IDPs, while no IDPs related to other modalities are found significant; in both cases the maximum IDP correlation only reached r=0.12, whereas the strongest association with BigFLICA modes was almost double this.…”
Section: Resultssupporting
confidence: 89%
“…5c ). There are several resting-state connectivity-related IDPs correlated with handedness ( Tables S3 ), consistent with a recent study 30 that also used UKB IDPs, while no IDPs related to other modalities are found significant; in both cases the maximum IDP correlation only reached r=0.12, whereas the strongest association with BigFLICA modes was almost double this.…”
Section: Resultssupporting
confidence: 89%
“…These observations have led to a number of studies investigating the role of handedness and brain asymmetries both in the context of human evolution and in cognitive abilities. Handedness has been investigated for association with cognitive skills, personality traits and psychiatric disorders (3)(4)(5). However, the cause/effect relationship between handedness, brain asymmetries and disorders remains unexplained and debated (6).…”
Section: Introductionmentioning
confidence: 99%
“…While very low levels of heritability pose methodological problems, the search for genetic variants continues, not so much with the goal of explaining large amounts of variance in handedness, but rather with the goal of illuminating the biological pathways involved in determining asymmetry. This can be feasible, provided there are suitable phenotypic measures available in very large samples Wiberg et al, 2019) It is possible that the same will prove to be the case for language lateralisation, especially given prior findings of significant heritability in structural measures of subcortical brain regions (Eyler et al, 2014;Guadalupe et al, 2017), cortical area and thickness (Kong et al, 2018) and language-related fibre tracts (Jahanshad et al, 2010), plus the large family study of Somers et al (2015) that used a binary phenotype, and the mixed findings on dichotic listening by Ocklenburg et al (2016). A further point to note is that different language tasks show different degrees of lateralisation (Woodhead et al, 2019), and we simply do not know which may be the most heritable.…”
Section: Discussionmentioning
confidence: 99%